BIOSYNTHESIS AND CHARACTERIZATION OF COPPER NANOPARTICLES USING MINT (MENTHA SPP.) LEAF EXTRACT - Ismail, Abdullahi; Adamu, Gambo Abdulbasid (FUDMA Journal of Sciences, 2026)
The green synthesis of copper nanoparticles (CuNPs) using Mentha (mint) leaf extract as a reducing and capping agent is reported in this study. The extract reduced copper sulfate under alkaline conditions to form stable CuNPs. UV-Vis spectroscopy revealed a surface plasmon resonance (SPR) peak at 240.01 nm, corresponding to a particle size of approximately 37.22 nm. Fourier-transform infrared (FTIR) spectroscopy identified key functional groups: 3304 cm⁻¹ (–OH), 1719 cm⁻¹ (C=O), 1149 cm⁻¹ (C–O), and 678 cm⁻¹ (C–H), confirming the role of mint phytochemicals in nanoparticle stabilization. Zetasizer analysis gave an average hydrodynamic diameter of 37.32 nm, indicating monodisperse distribution. These eco-friendly CuNPs show strong potential for catalytic, antimicrobial, and environmental remediation applications, supporting sustainable nanotechnological approaches.
Keywords: Copper Nanoparticles; Green Synthesis; Mint Extract; Surface Plasmon Resonance; Zetasizer